2018
DOI: 10.2147/oajc.s170150
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum family-planning barriers and catalysts in Burkina Faso and the Democratic Republic of Congo: a multiperspective study

Abstract: PurposeTo address the high unmet need for postpartum family planning (PPFP) in resource-limited settings, particularly in sub-Saharan Africa, this study aimed to identify PPFP-related barriers and catalysts to inform policies and programs to increase access to postpartum contraception.MethodsUsing qualitative methodology, we explored the perspectives of women, adolescent girls, men, religious and community leaders, service providers, and decision makers from three rural communities in Burkina Faso and three ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 42 publications
11
23
0
Order By: Relevance
“…In Burkina Faso, it was at 3 months postpartum for LARC and 2 for SARC, which contrasted with a much later adoption in DR Congo at more than 5 months postpartum for LARC and more than 8 for SARC. Our Yam Daabo formative research already revealed that women appeared to rarely attend the 6-week postpartum visit [15], which is con rmed by this secondary analysis. These ndings may have important implications to inform the revision of policies and practices in both countries and particularly DR Congo: under routine care, the 6-week postpartum visit dedicated to PPFP should be delayed to better match women's timing for PPFP adoption.…”
Section: Findings and Interpretationssupporting
confidence: 71%
“…In Burkina Faso, it was at 3 months postpartum for LARC and 2 for SARC, which contrasted with a much later adoption in DR Congo at more than 5 months postpartum for LARC and more than 8 for SARC. Our Yam Daabo formative research already revealed that women appeared to rarely attend the 6-week postpartum visit [15], which is con rmed by this secondary analysis. These ndings may have important implications to inform the revision of policies and practices in both countries and particularly DR Congo: under routine care, the 6-week postpartum visit dedicated to PPFP should be delayed to better match women's timing for PPFP adoption.…”
Section: Findings and Interpretationssupporting
confidence: 71%
“…So, one of the common reason for discontinuation given by women is their partner's opposition. This has already been reported in several studies [20][21][22][23][24] as one of the inhibitors for contraception use by women in general and especially by married women. The opposition from partners calls for more targeted action towards men to gain a better commitment from them to facilitate the use of contraceptive methods by women.…”
Section: Discussionsupporting
confidence: 54%
“…Reason of contraception discontinuation or switching: lastly, regarding the reason of contraception discontinuation or switching, some women did not indicate their reasons for the discontinuation and switching of methods (17 women in total, similar repartition between the study's group). This lack of clear reason raises questions, especially in an African context, marked by misconceptions about contraception, as shown in the rst phase of this trial [20]. A literature review by Blackstone et al, published in 2017 regarding factors in uencing contraceptive use in sub-Saharan Africa between 2005 and 2015 showed that negative factors prohibiting or reducing contraceptive use were women's misconceptions of contraceptive side-effects, male partner disapproval, and social/cultural norms surrounding fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for discontinuation given by women is the partner's opposition. This has already been reported in several studies [20][21][22][23] as one of the inhibitors for contraception use by women in general and especially by married women. The opposition from partners calls for more targeted action towards men to gain a better commitment from them to facilitate the use of contraceptive methods by women.…”
Section: Reason Of Contraception Discontinuation or Switchingsupporting
confidence: 56%
“…lastly, regarding the reason of contraception discontinuation or switching, some women did not indicate their reasons for the discontinuation and switching of methods (17 women in total, similar repartition between the study's group). This lack of clear reason raises questions, especially in an African context, marked by misconceptions about contraception, as shown in the rst phase of this trial [20]. In Benin, for example, Chae et al showed in 2014 that, among married women with unmet needs, opposition to contraceptive methods is one of the main reasons for not using contraception.…”
Section: Reason Of Contraception Discontinuation or Switchingmentioning
confidence: 99%